158 Non-invasive near-infrared flourescence imaging of malodialdehyde-oxidised low-density lipoprotein in atherosclerosis. (4th June 2021) - Pandey, Samata
Abstract : Introduction: Atherosclerosis is an insidious disease where the accumulation of low-density lipoprotein in the arterial walls generates plaques, which may rupture leading to an untimely death or loss of quality of life. A key barrier for the treatment of atherosclerosis is identifying and predicting those plaques which are most vulnerable to rupture. This project aimed to bridge this diagnostic gap by using monoclonal antibodies for targeted imaging of malondialdehyde-low density lipoprotein (MDA-LDL), a component of vulnerable plaques. Method: A humanised monoclonal antibody (LO1-huFab) was expressed in human embryonic kidney cells (HEK)-293 cells with an unpaired sulfhydryl group for site-specific maleimide conjugation. The purified protein was site-specifically conjugated to a near-infrared fluorophore (LO1-huFab-750) and one nanomole injected in LDL receptor-deficient (LDLR-/-) and wild-type (C57/BL6) mouse model. Mice were additionally co-injected with fluorophores targeting matrix metalloproteinases (MMPSense) and integrin a5b3 (IntegriSense). Non-invasive fluorescence molecular tomography imaging was performed four hours post-injection with the amount of the three different tracers in the aortic arch quantified. Results: LO1-huFab demonstrated in vivo targeting in LDLR-/- mouse model with the ability to distinguish animals with and without disease (63.16 ± 12.64 pmol vs 23.92 ± 4.35 pmol, p=0.045, n=4 per group). Multiplexing with MMPSense and IntegriSense revealed LO1-huFab-750 to be the first probe to distinguish between disease states. Ex vivo fluorescence reflectance imaging validated the focal signal of LO1-huFab-750 observed in the aortic root and abdominal aorta. Rapid clearance of LO1-huFab-750 through the glomerular filtration system was evident through ex vivo quantification of fluorescence in the kidneys. Conclusion: Site-specific near-infrared labeling of antibodies allowed for non-invasive imaging of atherosclerosis demonstrating its potential in identifying critical components of vulnerable plaques. These promising results have prompted the conjugation of LO1 antibody fragments with nanoparticles for targeted therapeutics of atherosclerosis. Conflict of Interest: N/A